Hemagglutinin protein of Asian strains of human influenza virus A H1N1 binds to sialic acid--a major component of human airway receptors - Chua, K.H.; Chai, H.C. (2012)
Hemagglutinin (HA) protein plays an important role in binding the influenza virus to infected cells and therefore mediates infection. Deposited HA sequences of 86 Asian strains of influenza A (H1N1) viruses during the first outbreak were obtained from the NCBI database and compared. Interaction of the HA protein of influenza A (H1N1) virus with the human sialic acid receptor was also studied using bioinformatics. Overall, not more than three single-point amino acid variants/changes were observed in the HA protein region of influenza A (H1N1) virus from Asian countries when a selected group sequence comparison was made. The bioinformatics study showed that the HA protein of influenza A (H1N1) binds to the sialic acid receptor in human airway receptors, possibly key to air-borne infection in humans.